DEPRESSION IN PATIENTS WITH AND WITHOUT POST-STROKE EPILEPSY - Perović, Zlatana K; Rosandic, Helena (Sanamed, 2025)
Introduction: Depression is the most common neuropsychological complication of stroke. It affects quality of life, prolongs hospitalization, and leads to more frequent doctor visits. The incidence of depression after stroke ranges from 18% to 33%. About 6–15% of patients develop epilepsy following stroke. Patients with post-stroke epilepsy tend to experience depression more frequently.Objective: The aim of this study was to compare the incidence of depression during the first year after stroke in patients who developed epilepsy versus those who did not.Patients and Method: We tested patients during the first year after stroke, treated at the Department of Neurology, General Hospital Nikšić, Montenegro. Two groups of 60 patients each were assessed: one group with post-stroke epilepsy and the other without epilepsy. Depression was measured using the Hamilton Depression Scale. Statistical analysis included mean values, t-test, and Chi-square test (χ²). A significance level of p < 0.05 was used for all tests.Results: The incidence of depression after stroke was high among our patients. Depression prevalence in the post-stroke epilepsy group was 55%, while it was 26.7% in the group without epilepsy.Conclusion: Patients with epilepsy have almost twice the incidence of depression compared to those without epilepsy after stroke (p < 0.05). These patients require special monitoring and more frequent follow-ups. Early detection of epilepsy and timely initiation of treatment with appropriate antiepileptic drugs, along with early management of depression, are important to prevent suicide and mortality and to improve quality of life.
Keywords: post-stroke depression; post-stroke epilepsy